2019
DOI: 10.1093/geroni/igz038.828
|View full text |Cite
|
Sign up to set email alerts
|

Personality Moderates Intervention Effects on Cognitive Function: A 6-Week Conversation-Based Intervention

Abstract: Conversation-based interventions have positive effects on cognitive health, though determining who benefits most is still unclear, and individuals’ personality may play a role. We utilized data from a 6-week randomized controlled trial to determine if conversation-based intervention effects were moderated by personality traits in 83 older adults (Mean age = 80.51 years, 49 cognitively intact, 34 with mild cognitive impairment). The intervention group participated in daily 30-minute face-to-face semi-structured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…17 The I-CONECT study examines whether enhancing social interaction via video chat can improve cognitive function. This study is an extension of the previous pilot trial 18,19 where efficacy was shown. The experimental group participates in 30-min video chats with trained conversational staff (4 times/week for the first 6 months, 2 times/week for additional 6 months) and weekly check-in telephone calls.…”
Section: Methodsmentioning
confidence: 89%
See 2 more Smart Citations
“…17 The I-CONECT study examines whether enhancing social interaction via video chat can improve cognitive function. This study is an extension of the previous pilot trial 18,19 where efficacy was shown. The experimental group participates in 30-min video chats with trained conversational staff (4 times/week for the first 6 months, 2 times/week for additional 6 months) and weekly check-in telephone calls.…”
Section: Methodsmentioning
confidence: 89%
“…Further, more research on the type of conversations and individual personality traits would increase our understanding of the emotional and structural needs of older adults with limited social interactions (e.g., relieving stress, catching up on news, reassuring of worth, needing instrumental help). 19 Finally, participants included in this study were free from severe depressive symptoms (operational criteria using the GDS-15) and dementia. Therefore, the generalizability of our study findings is limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interventions to improve social cognitive abilities, such as theory of mind or empathy in older people are generally lacking, and little work has been done in this area in people with cognitive disorders. The role of personality characteristics, such as agreeableness, conscientiousness and extraversion has been identified [50] but strategies to deal with this are yet to be examined.…”
Section: Social Capitalmentioning
confidence: 99%
“…Given the framework provided here, it would be an important next step to perform large randomized clinical trials specifically targeting the social domain to slow down the progression of AD. Possibly, the social intervention procedure requires thorough optimization and in humans possibly personalization, taking into account factors like personality traits and disease stage [59]. Based on the shared neurobiological substrates of the social domain and cognitive domain, we propose that adding more focus on the social domain may contribute to improving both social and cognitive functioning of AD patients.…”
Section: Implications For Treatment Strategies Of Psychiatric and Neu...mentioning
confidence: 99%